2018
DOI: 10.3390/app8040604
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Medical Mesh-Nebulizer for Aerosol Drug Delivery

Abstract: In the field of drug delivery, a nebulizer is a device used to convert liquid drugs into tiny airborne droplets, such as aerosol or a mist form. These fine droplets are delivered to a patient’s lungs and airways and then spread throughout the body via blood vessels. Therefore, nebulization therapy is a highly-effective method compared with existing drug delivery methods. To enhance the curative influence of a drug, this study suggests the use of a new micro-porous mesh nebulizer consisting of a controllable pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The results showed that lung deposition was significantly higher for the investigational vibrating mesh nebulizers in an in vitro model of a preterm infant of 32-weeks gestational age. Recently, Choi et al [20] manufactured a micro-porous mesh nebulizer with an optimized Pd-Ni membrane filter. Their results showed a good biocompatibility and an excellent durability which makes this nebulizer quite promising for its use in biomedical engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that lung deposition was significantly higher for the investigational vibrating mesh nebulizers in an in vitro model of a preterm infant of 32-weeks gestational age. Recently, Choi et al [20] manufactured a micro-porous mesh nebulizer with an optimized Pd-Ni membrane filter. Their results showed a good biocompatibility and an excellent durability which makes this nebulizer quite promising for its use in biomedical engineering.…”
Section: Introductionmentioning
confidence: 99%
“…This applies especially to newborns and infants. The role of mesh nebulizers, which generate homogeneous aerosol particles (monodisperse aerosol) and are characterized by low drug losses, short nebulization time and high predicted lung deposition, is becoming increasingly important [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that jet nebulizers generally decrease the reservoir’s solution temperature during the first 2 min of operation, whereas ultrasonic nebulizers increase the temperature by ~20 °C within a few minutes [ 45 ]. Mesh nebulizers are based on further development of the ultrasonic nebulization principle to improve aerosol generation efficiency, speed of nebulization, and device handling, as well as to reduce residual volumes; however, optimizing protein stability during nebulization has not been not a primary concern [ 31 , 46 ]. As research began to deliver expensive proteins directly into the lungs using a nebulizer, researchers examined whether proteins were stably nebulized with various type of nebulizers, because aggregation and degradation of proteins can reduce protein activity or even result in immunogenicity [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%